Influences of seepage into walls, curvature and bifurcation on pressure drop calculation in idealized arteries : A computational fluid dynamics approach / Govindaraju Kalimuthu - Govindaraju, Kalimuthu (2015)
Evaluation of physiological significance of coronary stenosis severity is of great importance than the anatomical significance to identify potentially ischemic stenosis for revascularization whereas non-culprit stenosis has been deferred from stenting. In a clinical settings, the functional severity of the stenosis is evaluated by fractional flow reserve (FFR) which is derived from mean pressure drop ( p ~  ) across the stenosis. The other parameters such as Pressure Drop Coefficient (CDP) and Lesion Flow Coefficient (LFC) which are derived from fluid dynamic principles also useful to evaluate the functional severity of the stenosis. The diagnostic accuracy of measuring severity of stenosis is enhanced by using small diameter guide-wire sensor under hyperemic flow condition. In the presence of stenosis, a cutoff value of FFR < 0.75 could almost induce myocardial ischemia, whereas FFR > 0.8 never associated with exercise-induced ischemia in a single vessel coronary artery disease (CAD) from numerous clinical trials. This means that the gray zone for FFR is between 0.75 and 0.80. In this thesis, a possible region of misinterpretation of stenosis severity was evaluated when it was assessed in vitro by considering the variations of FFR, CDP and LFC for a given percent area stenosis (AS) under the following three different cases. (i) The arterial wall and plaque region were considered as highly permeable to blood in the event of plaque rupture (ii) variations in the angle of curvature of the artery wall and (iii) variations in the bifurcation angle of coronary artery. In all the above cases without guide wire condition was considered. To understand the effect of porous media on the diagnostic parameters, A computational fluid dynamic simulations were carried out in rigid artery (RA) and Fluid porous Interface (FPI) stenotic artery wall models. The p ~  across the stenosis was compared for the given percent AS. The p ~  was lower in the FPI model than in the RA model. As a result, a changes in the diagnostic parameters exist for a given percent AS which leads to misinterpretation in the intermediate stenosis severity. The misinterpretation region was found to be 81.83 to 83.2% AS The influence of artery wall curvature i.e. 0°, 30°, 60°, 90° and 120° on the coronary diagnostic parameters have been studied. It was found that with increase in the curvature of the arterial wall for a given percent AS, the p ~  increases hence affects the FFR, CDP and LFC. These variations leads to misinterpretation in the evaluation of stenosis severity in vitro. The misinterpretation region was found to be 76.10 to 79.07% AS. The influence of bifurcation angulation i.e. 30°, 60° and 90° on the coronary diagnostic parameters have been studied. It was found that with increase in the angulation, the p ~  decreases hence affects the FFR, CDP and LFC. These variations leads to misinterpretation in the evaluation of stenosis severity in vitro. The misinterpretation region was found to be 81.8 % to 84.12% AS.